2000
DOI: 10.3109/13550280009030758
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterisation and infection of ovine microglial cells with Maedi-Visna Virus

Abstract: Maedi-Visna Virus (MVV) infection of the central nervous system (CNS) results in pathological changes, the mechanisms of which are poorly understood. MVV preferentially infects cell of the monocyte/macrophage lineage in vivo. The neuroparenchymal microglial cells are the resident tissue macrophages in the CNS and therefore likely targets for MVV infection. However, no information is currently available on the susceptibility of these cells to MVV infection or their contribution to neuropathological changes as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Previous studies of neural tissue from human patients with various immune‐mediated nervous system diseases have shown up‐regulation of CD1b on hypertrophic astrocytes in chronic active lesions of multiple sclerosis 19 and on endoneurial macrophages and myelinated nerve fibres in acute inflammatory demyelinating polyradiculoneuropathy 20 . Expression of CD1 by ovine microglial cell cultures has also been described 21 . The results described here confirm constitutive group 2 CD1 expression within the CNS of sheep.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous studies of neural tissue from human patients with various immune‐mediated nervous system diseases have shown up‐regulation of CD1b on hypertrophic astrocytes in chronic active lesions of multiple sclerosis 19 and on endoneurial macrophages and myelinated nerve fibres in acute inflammatory demyelinating polyradiculoneuropathy 20 . Expression of CD1 by ovine microglial cell cultures has also been described 21 . The results described here confirm constitutive group 2 CD1 expression within the CNS of sheep.…”
Section: Discussionsupporting
confidence: 83%
“…Expression of CD1 by ovine microglial cell cultures has also been described. 21 .The results described here con®rm constitutive group 2 CD1 expression within the CNS of sheep. Recent experiments using CD1 knockout mice have shown that CD1-reactive T cells are required for the development of systemic tolerance to antigen introduced to the immune-privileged site of the eye.…”
mentioning
confidence: 99%
“…However, prion diseases are extremely chronic diseases that take months to years to fully develop (61); thus, small changes in the rate of PrP Sc accumulation can potentially be significant following amplification over that extended time period. Furthermore, both PrP Sc and SRLV are present independently in the same cell types, e.g., macrophages (20,23,24,43,49), dendritic cells (24,31,53), and microglia (5,7,16,33 Sc more efficiently than the virus-free cells, most likely due to virusinduced changes in the cellular membranes (4). However, it remains to be determined whether similar mechanisms are induced by infections with retroviruses and other viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue culture medium from uninfected OSCs was used as a negative control. Virus titres were determined as described previously using OSCs as indicator cells (Ebrahimi et al, 2000). Titres were expressed as tissue culture infectious dose 50 % (TCID 50 ).…”
Section: Methodsmentioning
confidence: 99%